The prevalence of thyroid disorders during early pregnancy in China: the benefits of universal screening in the first trimester of pregnancy - Wang, Weiwei; Teng, Weiping; Shan, Zhongyan; Wang, Sen; Li, Jianxin; Zhu, Lin; Zhou, Jin; Mao, Jinyuan; Yu, Xiaohui; Li, Jia; Chen, Yanyan; Xue, Haibo; et al. (European journal of endocrinology, 2011)
ContextMaternal thyroid disorders during early pregnancy can influence pregnancy outcome and fetal development. The recent Endocrine Society Clinical Practice Guideline recommends a case-finding approach in which pregnant women who are at high risk for developing thyroid disease are tested.ObjectiveThe purpose of this study was to use the first trimester-specific reference intervals of thyroid-related hormones to explore the prevalence of thyroid dysfunction during early pregnancy and to analyze effectiveness of different screening strategies.DesignA multicenter cohort study.MethodA total of 2899 pregnant women were enrolled in this study during their first trimester of gestation. Levels of TSH, free thyroxine, free triiodothyronine, and thyroid peroxidase antibodies (TPOAb) were measured and thyroid disorders of pregnant women were diagnosed based on the first trimester-specific reference intervals.ResultsThe prevalence of hypothyroidism was significantly higher in the high-risk group than in the non-high-risk group (10.9 vs 7.0%, χ2=7.1, P=0.008). The prevalence of hyperthyroidism was not significantly different between the high-risk group and the non-high-risk group (2.7 vs 1.6%, χ2=2.27, P=0.13). Elevated levels of TPOAb and a personal history of thyroid disease increased the risk of thyroid dysfunction.ConclusionsA case-finding strategy for screening thyroid function in the high-risk group would miss about 81.6% pregnant women with hypothyroidism and 80.4% pregnant women with hyperthyroidism.